The Unrestricted Global Effort To Complete The Cool Trial - Andrew W. Kirkpatrick; Federico Coccolini; Matti Tolonen; Samuel Minor; Ruhi Fadzlyana Jailani (BioMed Central, 2024)
Indexed by WOS/ Scopus